Is South Africa lost at sea in the crininilisation of catfisning? a comparative analysis - Botes, Emshareed (University of the Witwatersrand, Johannesburg, 2024)
The infamous form of online impersonation, colloquially known as "catfishing," has become rife globally. Through the boom of technology, especially that of the internet that gave rise to social media- gaining access to other individuals, photographs, personal details, and virtual lives is as easy as pushing a button. Catfishing occurs when individual X utilises the photographs and/or identity ofY. X either pretends to be Y, or X acts as themselves online and utilises the photos ofY to falsify X’s true identity when X speaks to Z. Catfishing" generally comprises of impersonation. Still, it does not always comprise of fraud. Several states in the USA, namely; Oklahoma, California, Texas, and New York have criminalised online impersonation as an independent criminal offence from "fraud." Although South African law has delictual remedies and criminalises fraud, it lacks a criminal offence in relation to the impersonation of an individual online, as has been codified in the USA. This essay focuses on the criminalisation of online impersonation (also known as "catfishing") in South Africa through a comparative analysis with the USA, to the exclusion of delictual remedies available in South Africa. This analysis proposes to amend the Cybercrimes Act, with the inclusion of a new section to the Act that focuses specifically on the criminalisation of catfishing through the use of a “scaffolding approach™ to categorise the different crimes intrinsic to catfishing.
A research report submitted in fulfillment of the requirements for the Master of Laws, in the Faculty of Commerce Law and Management, School of law, University of the Witwatersrand, Johannesburg, 2025
Keywords: UCTD; CATFIS; CYBERCRINES ACT 19 OF 20RO; SDG-12: Responsible consumption and production; SDG-8: Decent work and economic growth